Discovery and optimization of novel constrained pyrrolopyridone BET family inhibitors. Issue 10 (1st June 2018) - Fidanze, Steven D.; Liu, Dachun; Mantei, Robert A.; Hasvold, Lisa A.; Pratt, John K.; Sheppard, George S.; Wang, Le; Holms, James H.; Dai, Yujia; Aguirre, Ana; Bogdan, Andrew; Dietrich, Justin D.; et al.
Graphical abstract: Highlights: Two novel series of conformationally constrained BET inhibitors have been prepared and characterized. Compounds in each series demonstrate single digit nanomolar potency in binding and cellular assays. Compounds in each series show inhibition of tumor growth in a mouse xenograft model. Abstract: Novel conformationally constrained BET bromodomain inhibitors have been developed. These inhibitors were optimized in two similar, yet distinct chemical series, the 6-methyl-1 H -pyrrolo[2, 3- c ]pyridin-7(6 H )-ones (A) and the 1-methyl-1 H -pyrrolo[2, 3- c ]pyridin-7(6 H )-ones (B). Each series demonstrated excellent activity in binding and cellular assays, and lead compounds from each series demonstrated significant efficacy in in vivo tumor xenograft models.